Implementasi Kegiatan Keagamaan Dalam Meningkatkan Kecerdasan Spiritual Siswa - Imam Syafi'i; Mardiyah Mardiyah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Religion is a very sacred and sensitive matter, every regulation and religious activity organized by the school will be more fully complied with and the implementation will be more effective. The implementation of religious activities in schools is often associated with efforts to build the character and spirituality of students so that they become more religious and Islamic. This study was conducted through field research using a descriptive qualitative approach at MTs Darul Hasan Lajing Arosbaya Bangkalan. The results of the research findings explained that the dhuha and midday prayer programs in congregation are implementation practices that are proven to build an attitude of love for God, discipline, and istiqomah in students at school. The love for Allah SWT is realized by the more active the students carry out ritual activities both sunnah and obligatory. Meanwhile, disciplined behavior is shown by the more orderly and diligent participation of students in learning and religious activities both at school and in the community. This discipline brings istiqomah behavior, tawadu', cooperation, and mutual respect between friends, and cares more about the surrounding environment. This change in behavior is a real portrait of lifelong education that emphasizes the spiritual transformation of students.